The Relationship of Form-Function-Life in a Traditional Anatolian Housing - Sağlam, Temel (Journal of History Culture and Art Research, 2024)
In recent studies, it has been revealed that building art forms and especially housing formations are affected by many variables. In the architectural pattern, the form is developed by following the function, which arises from the socio-cultural need of the human being. For this reason, housing formations have emerged not only as a result of physical effects or factors, but also as a result of the suppression or manipulation of all social life factors. The traditional Anatolian house is the product of material culture accumulation formed by the determination of the life style experienced for many years. It is a reflection of the individual’s personality and worldview with its material, form and equipment. The "middle space", which is the focus of all the activities of the home life in the Anatolian residence, has a reference volume; It became the main determinant of the plan by transforming into an outer courtyard in warm climates, life in temperate regions, and a tandoori house in cold climates. The rich historical culture of the geography where the house was built has also been one of the shape determinants of the formal structure. The division of the harem-salon, which is formed due to the religious sensitivity brought by the belief in privacy, is also the agent of the furnishing of the interiors of the rooms and the shaping of the room elements. The structure of Anatolian houses, which were created with the principle of the generality of a single form and a single structure, is simple and can be read from the outside. The Anatolian house is built with an architectural style that is suitable for life, nature and environmental conditions, and instead of struggling with nature, it adapts to it and participates in the life cycle of nature. The construction methods of the Anatolian house are based on the principle of convenience and the dimensions are determined on the basis of human dimensions. In Anatolian housing construction, where the direction of the facades is determined by considering even the direction of the wind, the houses face the sunrise. Anatolian residences, built with the nobility of simplicity, have captured the aesthetics on the facades with the contrast of occupancy-space, gradation and depth of projection. This study aims to increase the recognition of traditional Anatolian residential architecture, which has emerged as a result of long historical experiences, and to create exemplary applications for future residential building designs. The study questions the function factor that determines the formation of the building elements, including the selection and planning of the place where the traditional Anatolian house will be built, and its relations with life. In addition, in the study, an answer is sought to the question of why the traditional Anatolian house is the type of building desired by the society.